Development of Teaching Materials in The Form of Comics Based on Local Wisdom Wave Material - Chercules Chercules; L Hakim; Lefudin Lefudin (Universitas Lambung Mangkurat, 2021)
This study aims to develop teaching materials of comics based on local wisdom of Sriwijaya country on wave material in class VIII SMPN 15 Palembang. The research method used was Research and Development (R&D) with the ADDIE model. The study was only until the stage of Analysis, Design, and Development (ADD). The subject of this research was conducted at SMPN 15 Palembang by involving 11 students of class VIII. This research consists of 3 stages, namely the analysis stage, the design stage, and the development stage. The implementation and evaluation stages were not carried out due to limited research time. Data analysis of student needs was measured through observation activities. The questionnaire was used to determine the feasibility of teaching material products based on expert validation and student responses. This prototype was then validated by construct and content experts from Raden Fatah State Islamic University Palembang and PGRI Palembang University. The results showed that the teaching material product was feasible based on expert validation with the category (80% - 89%) valid and supported by student responses with the category (75.1% - 100%) very practical. Due to time constraints, the problem of productive teaching materials for the implementation and evaluation stages was not carried out. Therefore, this research can be developed or continued in further research that has been studied on the limitation of the problem. It is hoped that researchers can develop this research according to the study of the ADDIE research model until the implementation and evaluation stages are completed.